Dietary Grape Seed Proanthocyanidin Alleviates the Liver Injury Induced by Long-Term High-Fat Diets in Sprague Dawley Rats - Sun, Hao Yang; Gu, Ai Xin; Huang, Bi Ying; Zhang, Tong; Li, Jian Ping; Shan, An Shan (Frontiers in Veterinary Science, 2022)
In mammal, liver is the most important organ that plays vital function in lipid metabolism. Grape seed proanthocyanidin (GSPE) is a kind of natural polyphenolic compounds primarily obtained from grape skin and seeds. Recent progress found it had highly bioavailability in defending obesity, hyperlipidemia, inflammatory, oxidative stress, and targeting on liver tissue. However, the mechanism of GSPE on high-fat (HF) dietary induced obesity was not fully understood, particularly the influences in liver functions. Therefore, the aim of this study was to investigate the effects of GSPE supplementation on the liver function and lipid metabolic parameters in those rats fed long-term of HF diets. A total of 40 healthy female Sprague Dawley rats were employed. After 8-weeks obesity model feeding, rats were randomly divided into four treatments: NC, standard diet; NC + GSPE, standard diet + 500 mg/kg body weight GSPE; HF, high fat diet; HG + GSPE, high fat diet + 500 mg/kg body weight GSPE. Results indicated that long-terms of HF feeding caused severe liver problems including megalohepatia, steatosis, inflammation, and hepatocyte apoptosis. The supplementation of GSPE alleviated these symptoms. The results of the current experiment sustained that GSPE addition up-regulated the expression of Wnt3a/β-catenin signaling pathway, thereby restrained the liver cell endoplasmic reticulum stress and hepatocyte apoptosis. Furthermore, the microRNA-103 may play roles in this signal-regulated pathway. In summary, GSPE observed liver protective effects and the current experiment provided a reference for the application in the treatment and prevention in human.